2016
DOI: 10.1016/j.tjo.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous suprachoroidal hemorrhage: Case report and review of the literature

Abstract: We present the clinical course, management, and final outcome of spontaneous suprachoroidal hemorrhage (SSCH) in an age-related macular degeneration (AMD) patient—a 64-year-old male receiving antiplatelet therapy who developed SSCH during the Valsalva maneuver. In addition to our case study, we discuss the results of a systemic review of the literature and reference lists of retrieved studies published from January 2001 to December 2013. Among a total of 31 patients (32 eyes), acute secondary glaucoma was a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Local or systemic application of corticosteroids to reduce intraocular inflammation, and the use of carbonic anhydrase inhibitors, sedatives, etc ., can be applied according to systemic conditions. Surgical treatment should be taken in the cases with a large amount of bleeding in the suprachoroidal space, especially the generation of kiss signs, difficult to control high IOP, persistent pain, and patients with other vitreoretinal complications (such as a large amount of vitreous hemorrhage, retinal detachment, or retinal incarceration)[18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Local or systemic application of corticosteroids to reduce intraocular inflammation, and the use of carbonic anhydrase inhibitors, sedatives, etc ., can be applied according to systemic conditions. Surgical treatment should be taken in the cases with a large amount of bleeding in the suprachoroidal space, especially the generation of kiss signs, difficult to control high IOP, persistent pain, and patients with other vitreoretinal complications (such as a large amount of vitreous hemorrhage, retinal detachment, or retinal incarceration)[18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for spontaneous SCH are almost identical to postoperative SCH, with the exception of anti-coagulant use. A meta-analysis showed that abnormal coagulopathy and the use of anti-coagulants were both major risk factors in spontaneous SCH in patients aged over 60, associated with 82.6% and 69.6% of the cases respectively [32]. With regards to use of warfarin, spontaneous SCH can occur when the INR is within or over therapeutic range [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous suprachoroidal haemorrhage (SSCH) is a rare entity and has been known to be associated with anticoagulation therapies (including warfarin, aspirin, clopidogrel, heparin), thrombolytic drugs (streptokinase, tissue plasminogen activator), blood dyscrasias, haemodialysis and Valsalva manoeuvre 2. Systemic predispositions include hypertension, atherosclerosis, cerebrovascular attack, coronary artery disease, diabetes mellitus, chronic renal failure, hepatic failure and disseminated intravascular coagulation 2.…”
Section: Descriptionmentioning
confidence: 99%
“…Systemic predispositions include hypertension, atherosclerosis, cerebrovascular attack, coronary artery disease, diabetes mellitus, chronic renal failure, hepatic failure and disseminated intravascular coagulation 2. Ocular associations are age-related macular degeneration, glaucoma, high myopia and proliferative diabetic retinopathy 2. Hypertension alone has been reported to cause SSCH with secondary angle closure glaucoma 3.…”
Section: Descriptionmentioning
confidence: 99%